1996
DOI: 10.1093/infdis/174.5.954
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Human Immunodeficiency Virus Vaccine Trials in Homosexual Men in the United States: Risk Behavior, Seroincidence, and Willingness to Participate

Abstract: Human immunodeficiency virus (HIV)-seronegative high-risk homosexual men were enrolled in a vaccine feasibility study in three US cities. HIV seroincidence was 2.3/100 person-years (95% confidence interval [CI], 1.7-2.9) over 18 months in 1975 men. After receiving an explanation of HIV vaccine trial design, 37% stated they were "definitely" willing to participate in future trials; seroincidence was 3.7/100 person-years (95% CI, 2.5-4.9) in this subgroup. An additional 57% "might be" or were "probably" willing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(43 citation statements)
references
References 32 publications
1
41
1
Order By: Relevance
“…This result was not consistent with findings from some previous studies, which suggested a positive association between HIV-related risk behaviors and WTP (Buchbinder et al, 1996;Gross et al, 2000;Hays & Kegeles, 1999). A negative association was reported previously in one vaccine trial among young Thai men, which found that having sex with sex workers was associated with diminished WTP (Jenkins et al, 2000).…”
Section: Discussioncontrasting
confidence: 82%
See 2 more Smart Citations
“…This result was not consistent with findings from some previous studies, which suggested a positive association between HIV-related risk behaviors and WTP (Buchbinder et al, 1996;Gross et al, 2000;Hays & Kegeles, 1999). A negative association was reported previously in one vaccine trial among young Thai men, which found that having sex with sex workers was associated with diminished WTP (Jenkins et al, 2000).…”
Section: Discussioncontrasting
confidence: 82%
“…Lower educational attainment was found to be related with greater willingness (Bartholow et al, 1997;Koblin et al, 1998;Perisse et al, 2000). Although in many developing countries there were concerns that women might be reluctant to be tested because of the fear of coping with a positive result (Temmerman, Ndinya-Achola, Ambani, & Piot, Bartholow et al (1997) to be more willing to participate in HIV vaccine trials.Previous studies have demonstrated a consistent positive association between HIV-related risk behaviors and WTP (Bartholow et al, 1997;Buchbinder et al, 1996;Gross et al, 2000;Hays & Kegeles, 1999). However, it is worthwhile to note that not all risk behaviors are associated with greater willingness.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Finally, trial participants may not be representative of other MSM, and caution should be used in generalizing our results. Indeed, if highrisk MSM tend to enrol in vaccine trials, 1,9,10 regression to the mean could explain reductions in sexual risk behaviours that might be reported from vaccine trials lacking a comparison group that receives neither vaccine nor placebo.…”
Section: Discussionmentioning
confidence: 99%
“…In the studies of retention in MSM, Whites were generally used as a comparison group, and non-White race/ethnicity was associated with loss to follow-up in minority MSM compared with Whites. 32,33,44,47,48 In addition, the study by Bartholow et al also found that MSM of "Other" ethnicities were more likely to be lost to follow-up than MSM who were African-American or Latino at 18 mo. 33 In the only study in which the population was predominantly IDU, completion at 18 mo was not related to race/ethnicity.…”
mentioning
confidence: 97%